2020
DOI: 10.1002/jmv.25894
|View full text |Cite
|
Sign up to set email alerts
|

Case fatality rate analysis of Italian COVID‐19 outbreak

Abstract: The Italian outbreak of COVID-19 cases is a public health emergency and there is a worldwide tremendous interest in the evaluation of the Italian epidemic evolution.Indeed, from February 2020, Italy is facing an explosion of COVID-19 cases. In particular, the Italian observed case fatality rate (CFR) is much higher than the other countries. Recently, it has been hypothesized that the extensive number of intergenerational contacts-typical of Italian culture-could contribute to explain the high number of deaths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 14 publications
3
39
0
1
Order By: Relevance
“…The overall case fatality rate (CFR) of COVID-19 has been estimated be ~0.7% (95% confidence interval (CI): 0.4–1.0) and to range from 0.001% to 10.1% among those under 20 and over 80 years of age, respectively [ 7 ]. Moreover, it has been reported that the CFR can reach as high as 17% in the Northern regions of Italy [ 8 ]. In China, Yan-ni and colleagues estimated the CFR to be 6.1 ± 2.9% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall case fatality rate (CFR) of COVID-19 has been estimated be ~0.7% (95% confidence interval (CI): 0.4–1.0) and to range from 0.001% to 10.1% among those under 20 and over 80 years of age, respectively [ 7 ]. Moreover, it has been reported that the CFR can reach as high as 17% in the Northern regions of Italy [ 8 ]. In China, Yan-ni and colleagues estimated the CFR to be 6.1 ± 2.9% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing COVID-19 deaths across countries, however, is challenging. Most of the existing literature has relied on case-fatality rates (CFR) as a measure of mortality (2)(3)(4)(5), which are not informative for international and historical comparisons. Since casefatality rates are calculated as the number of deaths divided by the number of confirmed cases, the absence of accurate estimation of the infection rates in a reference population makes the denominator in the CFR reliant on testing strategies and capacities (6).…”
Section: Introductionmentioning
confidence: 99%
“…To explore the current status of the global COVID-19 pandemic, in terms of CFR, data for the last 6 weeks (May 2, 2020 through June 6, 2020), retrieved from the WHO website 1 , were processed by naive as well as linear regression model analysis, as stated above 8,11,12 .…”
Section: Methodsmentioning
confidence: 99%